2016
DOI: 10.4172/2157-7420.1000217
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised Single-Blinded Controlled Trial on the Effectiveness of Brief Advice on Smoking Cessation among Tertiary Students in Malaysia

Abstract: Introduction-Tobacco smoking, a habitual behavior, is addictive and detrimental to health. Quitting requires personal abilities and environmental opportunities and therefore, improving these abilities and opportunities will undoubtedly act on smokers' motivation to quit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…There are few studies testing VBA delivered by healthcare providers in LMIC settings for comparison [ 27 , 32 ]. However, two small studies conducted in Malaysia [ 33 ] and China [ 34 ] reported a 15% quit rate in smokers unselected by motivation or pre-existing health condition at 6 and 12 months, respectively. This suggests that absolute quit rates in North Macedonia may be particularly low, and more work is required to understand how to increase the impact of VBA from physicians in this context.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies testing VBA delivered by healthcare providers in LMIC settings for comparison [ 27 , 32 ]. However, two small studies conducted in Malaysia [ 33 ] and China [ 34 ] reported a 15% quit rate in smokers unselected by motivation or pre-existing health condition at 6 and 12 months, respectively. This suggests that absolute quit rates in North Macedonia may be particularly low, and more work is required to understand how to increase the impact of VBA from physicians in this context.…”
Section: Discussionmentioning
confidence: 99%